Design of a Reference Buffer for a Delta-Sigma ADC with Current DAC - Castilho, Miguel Alexandre Leandro (2020)
In analog to digital conversion, it’s necessary to provide a reference voltage to the Analog to Digital Converter (ADC), in order to quantify the input signal. However, as the ADC has a switch constantly commuting on its input it will cause perturbations on the reference voltage provided by the Bandgap circuit. Thus, it will interfere with the normal behaviour of the Bandgap circuit, which will longer be capable of provide the desired reference voltage. Besides, if the reference voltage is not constant in the desired value the output code generated by the ADC will have errors. In order to avoid conversion errors it will be needed to introduce a buffer between the Bandgap and the ADC. Thus, taking advantage from the characteristics of the buffer (low output impedance, high input impedance and unitary gain) the system will be capable of recover from the perturbations introduced by the ADC in the reference voltage. Therefore, in this thesis are studied some of the already existing architectures of buffers, in order to see the advantages and disadvantages of each one. This way were chosen the best three architectures from a theoretical point of view, to implement and simulate, to obtain all the needed information in order to better compare them.